MODEL IDENTIFIKASI GAYA BELAJAR SISWA BERKEBUTUHAN KHUSUS PADA SISWA SEKOLAH ALAM PRINGSEWU DENGAN KONSEP SMART LEARNING - Anggraeni, Leni; Aprianto, Rudi; Muslihudin, Muhamad (STIT AL MULTAZAM, 2023)
Special Elementary Schools (SDLB), and Integrated Education, specifically for higher education levels, are not yet available. PP No. 17 of 2010 Article 129 paragraph (3) stipulates that students with disabilities consist of students who are: visually impaired; deaf; speech impaired; mentally disabled; quadriplegic; tunable; learning difficulties; slow to learn; Autistic. This research will focus on developing a learning identification model for SLB students with the development of Android-based information technology. To achieve an optimal student learning process, an expert system identification application for learning styles for students with disabilities was designed using an Android-based Expert System with a combination of the Forward Chaining method. The development of learning style identification was carried out at the Pringsewu Natural School using a software prototyping design model with desktop and online concepts. It is hoped that the combination of applications and tools will provide convenience for users, namely schools and teachers. Implementation of an Android-based digital system with a combination of an Expert System with the Forward Chaining Method with software design using Use Case Diagrams. This application will be a medium for measuring learning styles that is more effective and efficient and has high accuracy by testing results using black box testing. The system used to describe the model and flow of this application is Use Case Diagrams, Activity Diagrams, and Class Diagrams and uses a combination of decision trees with the Expert Forward Chaining concept with the Smart Learning concept. From the test results of the application used, the system was declared feasible and good with an accuracy of 97% using it.